Consulta foniátrica: relações entre um conjunto de provas e dificuldades escolares - Kencis, Carolina Christofani Sian (2021)
Introduction: Learning disability has significant relevance and can generate negative social impacts in the future of an individual if not corrected in time, phoniatrics is an area of otorhinolaryngology responsible for evaluating, diagnosing and referring for therapy and / or complementing the multidisciplinary diagnosis in these cases. Objective: to evaluate in students the association between the application of a set of tests used in the phoniatric assessment and complaints of schooling, and to identify which would be the main association relationships with academic performance when applied individually. Method: Cross-sectional study, blind and subdivided into 4 stages. In the 1st stage 66 children in the third year of elementary school were submitted to the set of tests of skills applied by the physician, in the 2nd stage the physician questioned the educators about complaints of school difficulty in the students, in the 3rd stage was obtained the school grade in Portuguese language of these students and in the 4th stage an analysis was made between the data. Results: The educator identified complaints of school difficulties in 27.2% of the 66 students. There was a statistically significant association between school difficulties and the following competency tests: Dictation of words and pseudowords, Dictation of words, Dictation of pseudowords, Rhyme, Phonemic synthesis, and in the reading test; fluency, intonation and understanding of the text and morals. In the multivariate logistic regression analysis of the tests: Word dictation, intonation in reading and understanding of the moral of the story were selected to compose the final model, illustrated in this way, with greater association with the specialized complaint. Conclusion: The tests identified as most relevant in identifying school difficulties were: dictation of words, intonation in reading and understanding of the moral of the story. However, the other tests that comprised the phoniatric consultation allowed the observation of the individual and his abilities in functioning, leading to a better assessment of the case, in aspects not directly related to the pedagogical one